1981
DOI: 10.1111/j.1095-8649.1981.tb05819.x
|View full text |Cite
|
Sign up to set email alerts
|

The physiological responses of blood during thermal adaptation in three freshwater fish species

Abstract: Surotherodon mossambicus, Cyprinus curpio and Salmo gairdneri were acclimatized at temperatures of 15, 20 and 25'C in order to study physiological responses of blood to temperature fluctuations in the laboratory. Cyprinus curpio exhibited the greater ability to survive at these temperatures. Surotherodon mossumbicus experienced osmoregulatory collapse at 15" C which also occurred in trout at 25" C. This was associated with acid-base malfunction in the trout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 9 publications
2
15
1
2
Order By: Relevance
“…Furthermore, immature erythrocytes of teleosts are more effective in oxygen transport than when mature (Houston et al., 1996). Positive correlation between sea water temperature and haemopoiesis has been observed by Smit et al. (1981) in carp ( Cyprinus carpio ) and rainbow trout ( Oncorhynchus mykiss ), by Lie et al.…”
Section: Haematological Parametersmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, immature erythrocytes of teleosts are more effective in oxygen transport than when mature (Houston et al., 1996). Positive correlation between sea water temperature and haemopoiesis has been observed by Smit et al. (1981) in carp ( Cyprinus carpio ) and rainbow trout ( Oncorhynchus mykiss ), by Lie et al.…”
Section: Haematological Parametersmentioning
confidence: 97%
“…Furthermore, immature erythrocytes of teleosts are more effective in oxygen transport than when mature (Houston et al, 1996). Positive correlation between sea water temperature and haemopoiesis has been observed by Smit et al (1981) in carp (Cyprinus carpio) and rainbow trout (Oncorhynchus mykiss), by Lie et al (1989) in Atlantic cod (Gadus morhua), by Audet et al (1993) in G. morhua and American plaice (Hippoglossoides platessoides), and by Rauthan and Grover (1994) in hillstream fish (Barilius bendelisis). However, in the present study an increased haemopoiesis was observed in sea bass during the cold months obscured this correlation.…”
Section: Haematological Parametersmentioning
confidence: 98%
“…Nos résultats pourraient confirmer cette dernière hypothèse puisque d'une façon générale, chez toutes les espèces, le taux de glucose sanguin paraît atteindre un maximum au début de la période estivale, soit au solstice d'été, et un minimum en novembredécembre, soit au solstice d'hiver. Cependant, l'augmentation plus ou moins précoce selon l'espèce, observée durant la période hivernale, peut être en relation avec les basses températures (4,8 O C en janvier, 2 O C en mars) (Love, 1970(Love, , 1980Smit et al, 1981).…”
Section: Glycémieunclassified
“…Protein synthesis rates have been found to be affected by temperature with Q~0 values ranging from 2 to 20 depending on the species, tissues or the temperature ranges (Haschemeyer et al 1979;Smith et al 1980;Fauconneau 1984). Drawing on data obtained by Kaushik (1981) and Fauconneau and Arnal (1985), it can be shown that an increase in temperature increases intake, protein synthesis n 10"C 180C Fig.…”
Section: Qualitative Changesmentioning
confidence: 93%